Nutritional characterization of the native fish Eleotris picta - Belmonte-Romo, Aldo Emmanuel; Barreto-Curiel, Fernando; Vega-Villasante, Fernando; Martínez-Franco, Alondra Nayeli; Aguirre-García, Zinnia Edith; Badillo-Zapata, Daniel (Ecosistemas y Recursos Agropecuarios, 2025)
The spotted sleeper (Eleotris picta), a native fish of the tropical eastern Pacific, shows a promising nutritional profile for its potential use in aquaculture. This study evaluated its bromatological composition, including meat-to-bone ratio, protein, fat, carbohydrate, ash content, as well as amino acid and fatty acid profiles. A carcass yield of 88.4 ± 1.2% and fillet yield of 23.1 ± 12.6% were obtained, values comparable to those of commercial species such as Oreochromis niloticus, Oncorhynchus mykiss, and Ictalurus punctatus. On a dry matter basis, the fillet contained 77.1 ± 18.2% protein and 2.3 ± 1.3% lipids. Lysine content reached 13.3 ± 5.2%, surpassing that of other freshwater species. Additionally, the lipid profile showed 10.4 ± 0.3% fatty acids, with high levels of EPA and DHA. These results support the potential of E. picta as a valuable alternative for the diversification of freshwater aquaculture species.
Keywords: Aquaculture nutrition; production performance; amino acids; fatty acids; native species